1994
DOI: 10.1002/net.3230240602
|View full text |Cite
|
Sign up to set email alerts
|

Topological properties, communication, and computation on WK‐recursive networks

Abstract: Recently, with the support of the CAPRI (Concurrent Architecture and PRogramming environment for highly Integrated system) project, Vecchia and Sanges proposed a new general class of recursively scalable networks, termed WK-recursive networks, and developed routing and broadcasting algorithms on them. They have also implemented the WK-recursive networks using VLSl technology. This paper studies WK-recursive networks by first investigating their topological properties such as diameter, connectivity, and Hamilto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…. , m 1 ) is node-symmetric when m n Å m n01 Å rrr Å m 1 , we obtain works can be found in [8,12]. Among them, W K(d, t) has diameter 2 t 0 1 and connectivity d 0 1.…”
Section: Generalized Hypercubesmentioning
confidence: 96%
See 1 more Smart Citation
“…. , m 1 ) is node-symmetric when m n Å m n01 Å rrr Å m 1 , we obtain works can be found in [8,12]. Among them, W K(d, t) has diameter 2 t 0 1 and connectivity d 0 1.…”
Section: Generalized Hypercubesmentioning
confidence: 96%
“…, where 1°m°d and Duh [8] showed that Algorithm 3.1 can produce the 0 1 and 1°i°t. Then, there exist m node-disjoint shortest routing path when u Å i £ and u is an i-frontier.…”
Section: E Wk-recursive Networkmentioning
confidence: 98%
“…The reader is referred to [2,4,7,13,22,25] for the details. The vertex set of S(n, k) consists of all n-tuples of integers 1, 2, .…”
Section: Sierpiński-like Graphsmentioning
confidence: 99%
“…They offer a high degree of regularity, first proposed a heuristic routing algorithm [22] and an scalability, and symmetry which very well conform to a optimal broadcasting algorithm [23]. Chen and Duh [2] modular design and implementation of distributed systhen improved their work by presenting a shortest-path tems involving a large number of computing elements. A routing algorithm and another optimal, but simpler, VLSI implementation of a 16-node WK-recursive netbroadcasting algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…A routing algorithm and another optimal, but simpler, VLSI implementation of a 16-node WK-recursive netbroadcasting algorithm. The diameter, Hamiltonicity, and work was realized at the Hybrid Computing Research connectivity were also computed in [2]. Node-disjoint Center [22].…”
Section: Introductionmentioning
confidence: 99%